Silicon isotopes of deep sea sponges: New insights into biomineralisation and skeletal structure - Cassarino L. (2018)
The silicon isotopic composition (30Si) of deep sea sponges' skeletal element - spicules - reflects the silicic acid (DSi) concentration of their surrounding water and can be used as natural archives of bottom water nutrients. In order to reconstruct the past silica cycle robustly, it is essential to better constrain the mechanisms of biosilicification, which are not yet well understood. Here, we show that the apparent isotopic fractionation (30Si) during spicule formation in deep sea sponges from the equatorial Atlantic ranges from ĝ'6.74 ‰ to ĝ'1.50 ‰ in relatively low DSi concentrations (15 to 35 μM). The wide range in isotopic composition highlights the potential difference in silicification mechanism between the two major classes, Demospongiae and Hexactinellida. We find the anomalies in the isotopic fractionation correlate with skeletal morphology, whereby fused framework structures, characterised by secondary silicification, exhibit extremely light 30Si signatures compared with previous studies. Our results provide insight into the processes involved during silica deposition and indicate that reliable reconstructions of past DSi can only be obtained using silicon isotope ratios derived from sponges with certain spicule types. © Author(s) 2018.